Strategi Pondok Pesantren Al Ma’ruf Kediri Dalam Mencegah Paham Radikalisme Agama - Feri Ferdian; Bustomi Mustofa (Tribakti: Jurnal Pemikiran Keislaman, 2019)
The radicalism movement that has taken root in the present must be prevented. Anti-radicalism education can be used as an effort to prevent the development of terrorism and radicalism in Indonesia. The values ​​of anti-religious radicalism in Islam originating from the Qur'an and Hadith are integrated into subjects in Islamic boarding schools. The concept of anti-radical Islam such as prohibiting killing, doing damage, and the command to do love for fellow human beings in the material taught. Anti-radicalism education requires the santri to respect differences. Thus, it can indirectly break the radicalism movement in Indonesia. The research method in this paper uses a qualitative approach, in collecting data using the method of observation, interviews and documents. While the data analysis technique uses editing, verifying and analyzing analysis techniques. The results of this study are the Strategies of Al Ma'ruf Islamic Boarding School in preventing 3 types of religious radicalism, namely: Exemplary Strategy, Coaching Strategy and Habit Strategy.